Developing energy efficient lignin biomass processing – towards understanding mediator behaviour in ionic liquids. (26th May 2016) - Eshtaya, Majd; Ejigu, Andinet; Stephens, Gill; Walsh, Darren A.; Chen, George Z.; Croft, Anna K.
Abstract : Environmental concerns have brought attention to the requirement for more efficient and renewable processes for chemicals production. Lignin is the second most abundant natural polymer, and might serve as a sustainable resource for manufacturing fuels and aromatic derivatives for the chemicals industry after being depolymerised. In this work, the mediator 2, 2′-azino-bis(3-ethylbenthiazoline-6-sulfonic acid) diammonium salt (ABTS), commonly used with enzyme degradation systems, has been evaluated by means of cyclic voltammetry (CV) for enhancing the oxidation of the non-phenolic lignin model compound veratryl alcohol and three types of lignin (organosolv, Kraft and lignosulfonate) in the ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate, ([C2 mim][C2 SO4 ]). The presence of either veratryl alcohol or organosolv lignin increased the second oxidation peak of ABTS under select conditions, indicating the ABTS-mediated oxidation of these molecules at high potentials in [C2 mim][C2 SO4 ]. Furthermore, CV was applied as a quick and efficient way to explore the impact of water in the ABTS-mediated oxidation of both organosolv and lignosulfonate lignin. Higher catalytic efficiencies of ABTS were observed for lignosulfonate solutions either in sodium acetate buffer or when [C2 mim][C2 SO4 ] (15 v/v%) was present in the buffer solution, whilst there was no change found in the catalytic efficiency of ABTS in [C2 mim][C2 SO4 ]–lignosulfonate mixtures relative to ABTS alone. In contrast, organosolv showed an initial increase in oxidation, followed by a significant decrease on increasing the water content of a [C2 mim][C2 SO4 ] solution.